2017
DOI: 10.1002/cctc.201700272
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Squaramides as Organocatalysts for Lactide Polymerization: Catalytic Performance and Comparison with Monofunctional Analogues

Abstract: Amine‐functionalized squaramides 1 and 2 were prepared and shown to be suitable polymerization organocatalysts for the controlled ring‐opening polymerization (ROP) of l‐lactide (l‐LA) in the presence of an alcohol source such as BnOH (which acts as an initiator) to afford chain‐length‐controlled and narrow‐dispersion poly(l‐lactide) (PLLA) under mild reaction conditions. The ROP experimental and polymer analysis data are consistent with the action of 1 and 2 as bifunctional hydrogen‐bonding (HB) catalysts that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 69 publications
(38 reference statements)
0
16
0
Order By: Relevance
“…In addition, the activity and controllability of catalysts can be further improved by using multiurea instead of monourea . In general, HBDs are tailored by electronic and steric effects of catalyst substituents to manipulate their catalysis performance . Typical electron withdrawing substituents of HBDs include trifluoromethyl and sulfonyl groups, which can enhance the electrophilicity of HBD moiety and facilitate the activation of the monomer's carbonyl group.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the activity and controllability of catalysts can be further improved by using multiurea instead of monourea . In general, HBDs are tailored by electronic and steric effects of catalyst substituents to manipulate their catalysis performance . Typical electron withdrawing substituents of HBDs include trifluoromethyl and sulfonyl groups, which can enhance the electrophilicity of HBD moiety and facilitate the activation of the monomer's carbonyl group.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this can be explained by the fact that the stronger interaction between H-bond donor and H-bond acceptor groups could neutralize their activating effects on the monomer and alcohol . (iv) It was also shown that bifunctional catalysts were faster in polymerization than monofunctional squaramides operated by adding a base such as a triethylamine externally . (v) It was found that the catalytic activity is extremely sensitive to substituents on both the squaramide part and the basic site.…”
Section: Introductionmentioning
confidence: 99%
“…11 The aforementioned obstacles to binary independent catalytic systems and the necessity of expensive HBA cocatalysts (such as (−)-sparteine) have prompted many researchers to investigate bifunctional systems (double action in a single molecule) providing polymerization without these disadvantages. 11,12 A stronger alternative to chiral thiourea catalysts is chiral squaramides, 13,14 showing H-bond donor Lewis acid activity like thioureas, as well. This type of bifunctional catalyst, first developed by Rawal et al in 2008, generally consists of a combined H-bond donor (Lewis acid, squaramide) and a Hbond acceptor (Brønsted base, amine) in the presence of a chiral scaffold 13 and catalyzes a wide range of organic reactions.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This proposed catalyst system bears many similarities to cooperative catalysis, with both acids and bases being present in the reaction mixture, often in equilibrium between the individual components and the homoconjugated species. While the field of cooperative catalysis in polymerization is established, especially regarding ring-opening polymerization of cyclic esters and carbonates, there are relatively few instances of cooperative catalysis to affect silanol polycondensation in the literature, and no mention of cyclosiloxane levels generated using these approaches. ,,, Homoconjugated acid catalysts are cheap, simple to make, relatively mild, and commercially available. This provides ample room to develop new catalyst compositions and explore how the base and acid component of the homoconjugate relate to reactivity and selectivity.…”
Section: Introductionmentioning
confidence: 99%